Survey of University-Based Music Programs in Canada - McLean, Don; Jobin-Bevans, Dean (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2009)
AbstractThis study provides a compact overview of university-based music programs in Canada based on information gleaned from surveys of institutional members of the Canadian University Music Society (CUMS)—universities, colleges, and conservatories. The surveys took place between 2005 and 2009. The current report focuses on the metrics of enrolment and staffing, and goes on to provide basic data on graduate and undergraduate programs. It is a first step in sharing information that can facilitate informed advocacy in support of music in higher education both within and beyond individual institutions.